Fintech and the Future of Banking: Collaboration and Innovation for Better Financial Services - Khuan, Hendri (Economics Studies and Banking Journal (DEMAND), 2024)
Collaboration between fintech companies and traditional banks is important for the evolution of the financial industry. Factors influencing fintech adoption by conventional banks include organizational culture, management attitudes and leadership. Understanding these factors is important for banks to remain competitive. Challenges to adoption include regulatory uncertainty, resource limitations, and data security issues, while opportunities include increased operational efficiency and greater consumer engagement. Factors influencing adoption also include technology sustainability, IT infrastructure, financial capabilities, human resources, government regulations, market changes, consumer behavior, industry competition, and strategic partnerships. Overcoming challenges such as cyber security risks and regulatory barriers, as well as capitalizing on opportunities through strategic partnerships and understanding consumer behavior, can drive successful fintech adoption for traditional banks.